A aplicação da Lei 9.966/2000 na prevenção e controle da poluição por óleo nos portos da costa marítima do Espírito Santo : estudo do Terminal Norte Capixaba - Amorim, Jader Luiz (2017)
The occurrence of oil spill incidents at sea in different countries have led for the development of systems to prevent oil pollution in marine waters. In Brazil, the Law n. 9.966/2000 is the main regulatory instrument on this matter. However, there are few studies with regard to this Law's applicability in a way that may contribute to a thorough investigation of the factors that lead to these incidents inside the Brazilian territory. In this context, the present study aimed to answer the following question: the oil pollution control and prevention system as mentioned in the Law n. 9.966/2000 is being applied effectively? In this way, a bibliographical and documentary research was conducted in order to investigate if the Law's requisites on prevention and control were being applied in the period from 2005 to 2014, in a sea terminal that moves oil in the state of Espírito Santo. So, the monitoring and control measures adopted by the designated environmental agency were verified; the data regarding oil spillage incidents taken place in the Terminal Norte Capixaba were checked; the penalties applied by the environmental agency and also the preventive and response actions shown by the company when undergoing oil spillage incidents at sea were analyzed. This research brings the conclusion that there is effort being made by the environmental agency for the application of preventive and control instruments established by the Law. However, company´s lack of compliance with legal deadlines allied to delayed analyses by the environmental agency involved may significantly result in low efficacy towards oil pollution prevention at sea.